MOTIVASI ORANGTUA DI JORONG SIGIRAN NAGARI MALALAK UTARA MELANJUTKAN PENDIDIKAN ANAKNYA DI PONDOK PESANTREN MADINATUL MUNAWWARAH - Zuria Murliadi; Charles; Wedra Aprison; Salmi Wati (Universitas Pahlawan Tuanku Tambusai, 2022)
The background of the problem in this study is the formulation of the problem, namely what motivates parents to continue their children's education at the madinatul munawwarah Islamic boarding school, what are the factors that encourage parents to continue their child's education at the madinatul munawwarah Islamic boarding school and what obstacles are faced by parents in continue their child's education. Therefore, researchers are interested in examining what motivates parents in Jorong Sigiran to continue their children's education at the Madinatul Munawwarah Islamic Boarding School. This type of research is descriptive qualitative that is describing what it is about a situation. In this study, the authors describe the motivation of parents in Jorong Sigiran Nagari Malalak Utara to continue their children's education at the Madinatul Munawwarah Islamic Boarding School. The data collection instruments used were observation, and interviews. Sources of required data obtained from informants, namely parents. The results of the study found that the motivation of parents in Jorong Sigiran Nagari North Malalak to continue their children's education at the Madinatul Munawwarah Islamic boarding school is so that children know more about religious knowledge, to become pious and pious children, to form noble character in children, to avoid environmental influences that not good, improve life. Efforts made by parents in continuing their children's education to the Madinatul Munawwarah Islamic Boarding School are motivating children, giving advice, giving punishment, educating, and giving examples. Keyword: Parents' Motivation